Does Environmental Enrichment with Music and Strobe Light Affect Broilers’ Welfare? Analyzing Their On-Farm Reaction - Jacob, Flavia Gerbi; Nääs, Irenilza de Alencar; Salgado, Douglas D’Alessandro [UNESP]; Baracho, Marta dos Santos; Lima, Nilsa Duarte da Silva; Pereira, Danilo Florentino [UNESP] (MDPI, 2022)
The present study observed whether environmental enrichment (music and strobe light) influenced farm-housed broiler chickens’ behavior. The trial was carried out on a commercial broiler farm from 21 to 35 days of growth. The sound stimulus consisted of playing a classical music track every day for an approximate length of 6 min, played five times a day for six weeks starting from the birds’ first day of age. The light stimuli came from a colored (red and green ground-projected dots) light-emitting diode (LED) strobe projector used after the musical stimulation. The broilers’ reaction was recorded (from day 21 through day 35), and individual bird behaviors were classified into welfare and stress. The birds’ ability to walk was measured using a gait score scale, and the degree of incidence of pododermatitis was verified. Environmental enrichment with light stimulus increased natural behavior in broiler chickens, such as eating, stretching, ground pecking, and flapping wings (p < 0.05). Broiler chickens tended to walk less in the housing with music stimuli (p < 0.05). In general, the environmental stimuli provided the birds with better walking ability but increased the incidence of pododermatitis (p < 0.01). We observed that the light stimulus left the birds more active; they foraged more and lay less when compared to the birds submitted to musical stimuli and the control. However, we also observed an increase in the frequency of stress-indicating behaviors in the environment under light stimulation. It is unclear whether broilers liked the tested stimuli of music and light in the scenarios studied. The enrichment with light or music apparently increased flock stress in 21- and 28-day-old broilers, with some benefit being observed only in 35-day-old broilers.
Keywords: environmental enrichment; precision livestock production; remote monitoring; stressful behavior; walking ability; welfare